A new terrestrial frog (Anura: Craugastoridae) from the montane cloud forests of the southeastern Ecuadorian Andes - Urgiles, Veronica L.; Posse, Valentina; Timbe, Bruno A.; Astudillo, Pedro X.; Sánchez-Nivicela, Juan C. (Zootaxa, 2017)
We describe a new species of Pristimantis from the Tinajillas-Rio Gualaceño Ecological Conservation Area, Morona Santiago province, an area of montane forest in the southeastern Andes of Ecuador. Pristimantis nimbus sp. nov. is similar to P. altamazonicus, P. ardyae, P. bambu, P. bellator, P. caeruleonotus, P. cethospilus, P. churuwiai, P. croceoinguinis, P. cryptomelas, P. diadematus, P. flavobracatus, P. gualacenio, P. nigrogriseus, P. ventrimarmoratus, and P. versicolor from which it can be distinguished by the presence of flash marks on flanks, groin, and arm insertion composed of bright-yellow oval spots and blotches surrounded by dark brown to black, forming a reticulated pattern, by having slightly enlarged toe pads, a finely shagreen dorsum lacking dorsal folds, and males having nuptial pads but lacking vocal slits. Pristimantis nimbus sp. nov. is only known from the type locality, at elevations between 2200–2400 masl. All individuals of the new species were found at night, perching on leaves and branches between 80 cm to 150 cm above the ground. The analysis of stomach contents rendered a total of 17 prey items of different unidentified species in five orders (Aranae, Coleoptera, Diptera, Hemiptera, Lepidoptera). Other species found in the area are Pristimantis aff. altamnis, P. galdi, P. proserpens, P. tinajillas, P. versicolor, Rhinella margaritifera, Noblella sp. and three unidentified species of Pristimantis.